Stability of bicortical screw versus plate fixation after mandibular setback with the bilateral sagittal split osteotomy: a systematic review and meta-analysis. Issue 1 (January 2016) - Al-Moraissi, E.A.M.; Ellis, E.
Abstract: The purpose of this study was to test the hypothesis that there is no difference in skeletal stability between bicortical screw and miniplate fixation after mandibular setback surgery with the bilateral sagittal split osteotomy (BSSO). A systematic and electronic search of several databases with specific key words, a reference search, and a manual search through September 2014 was performed. The inclusion criteria encompassed clinical human studies, including randomized controlled trials (RCTs), controlled clinical trials (CCTs), and retrospective studies, with the aim of comparing bicortical screw fixation to miniplate fixation after mandibular setback with the BSSO. Changes in both linear (horizontal and vertical) and angular measurements (SNB and mandibular plane) were analyzed. The initial PubMed search identified 317 studies, of which seven met the inclusion criteria—one RCT, four CCTs, and two retrospective studies. Bicortical screw fixation was found to provide slightly better skeletal stability than miniplate fixation after setback with the BSSO, but the difference was not statistically significant. The results of this meta-analysis support the hypothesis that there is no statistically significant difference in skeletal stability between bicortical screw fixation and plate fixation of the BSSO when used for mandibular setback.